About Sovereign Wealth Fund : Comparative Study Between Daya Anagata Nusantara and 1Malaysia Development Berhad - Nalasatya, Putiara (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sovereign Wealth Funds (SWFs) function as state-owned investment instruments designed to support macroeconomic stability and long-term development. Specific Background: Indonesia’s Danantara and Malaysia’s 1MDB represent two national models with shared objectives but divergent governance outcomes. Knowledge Gap: Despite Danantara’s strategic role in state-asset consolidation, limited research has compared its legal foundation and governance vulnerabilities with the failed 1MDB model. Aims: This study examines the governance structures, legal legitimacy, and oversight mechanisms of Danantara in comparison with 1MDB to identify potential risks. Results: Findings show that both institutions exhibit similarities in centralized executive control, ambiguous regulatory frameworks, and insufficiently independent auditing processes, creating vulnerabilities to conflicts of interest and weakened accountability. Novelty: This research provides an early, systematic legal-comparative assessment of Danantara, highlighting structural parallels with 1MDB before similar governance failures materialize. Implications: Strengthening Danantara’s sui generis legal basis, clarifying institutional status, and reinforcing checks-and-balances mechanisms are critical to preventing maladministration, ensuring transparency, and safeguarding national assets. Highlights: Danantara and 1MDB share governance risks rooted in concentrated executive authority. Weak legal frameworks and unclear institutional status heighten vulnerability to maladministration. Strengthening oversight, transparency, and checks-and-balances is crucial to prevent 1MDB-like failures. Keywords: Danantara, 1MDB, Sovereign Wealth Fund, Governance, Legal Accountability